Strengthening MBKM Ecosystem: A Comprehensive Approach through Satgas PPKS to Address Sexual Violence in Indonesian Higher Education - Azizatuz Zahro; Ritha F Dalimunthe; Ramadani Ramadani; Evi Eliyanah; Firlianti Firlianti; Desinta Dwi Rapita; Alfi A. Pulungan (Randwick International of Social Science Journal, 2024)
This research aims to strengthen the MBKM ecosystem through the PPKS Task Force in all Indonesian universities, in accordance with Permendikbudristek Number 30 of 2021. This initiative supports the concept of Independent Learning Campus Independence with a focus on freedom, innovation and independence. Sexual violence was identified as a major obstacle to creating an inclusive learning environment. The PPKS Task Force, like at USU, UM, and UPR, is collaborating with Puspeka to provide training and use creative media such as comics and videos to increase students' understanding and awareness regarding this issue. However, participation in PPKS socialization is still minimal, and this research suggests increasing the use of creative media to disseminate information. This study was conducted at seven universities in six provinces of Indonesia, using the Participatory Action Research method with the active participation of students, lecturers and education staff. The development of creative media, such as short films and short stories, is field tested to strengthen understanding regarding PPKS and build an inclusive and healthy educational environment. The research findings demonstrate the urgency of addressing sexual violence in higher education and recommend a more targeted and comprehensive awareness campaign to increase understanding and participation in PPKS initiatives throughout Indonesia.